La consueta de 1709 en escena: orígens i models d'una realitat canviant. - MASSIP, FRANCESC (Scripta, 2014)
This work analyses the oldest available manuscript from the Festa d'Elx, dated 1709 and copied to replace the one that had been preserved in the town archives and had been damaged in the sacking by the troops of Philip V in 1706. The copy is thought to have been made from the original in which the first folio or folios were missing due to the aforementioned damage. This original must have belonged to the manuscripts created by the Confraternity of the Assumption, before the Festa started to be organized by the Town Council. Moreover, this research looks into the stage reality as reflected in the stage directions of the Consueta (play manuscript) of 1709, which presents a layout that differs largely from the current one that corresponds to the new church built in the middle of the eighteenth century, in a scenic articulation that was initiated in 1761 by the architect Mark Evangelio.